Aquaporins modulate the cold response of Haemaphysalis longicornis via changes in gene and protein expression of fatty acids - Han Wang; Ruwei Bai; Tingwei Pei; Jianglei Meng; Chuks F. Nwanade; Yuchao Zhang; Xiujie Liang; Yunsheng Tang; Jingze Liu; Zhijun Yu (Parasites & Vectors)
Abstract Background As ectotherms that spend most of their life in the environment (off-host), ticks face challenges in maintaining water balance, and some species must cope with severe low winter temperatures. Aquaporins (AQPs) are essential membrane proteins that enhance cold tolerance in many animals by regulating homeostatic processes. However, the dynamic expressions and involvement of aquaporins in the cold stress of ticks remain unclear. Methods In the present study, three AQP genes, HlAQP2, HlAQP3, and HlAQP5, belonging to the major intrinsic protein (MIP) superfamily, were characterized from the important vector tick Haemaphysalis longicornis. Then, multiple bioinformatics analyses were performed. Quantitative real-time PCR (qPCR) was used to detect different expressions of H. longicornis genes under different cold treatment conditions. RNA interference was used to explore the relationship between AQP and the cold response of H. longicornis. Additionally, proteomic and transcriptomic analyses were used to investigate the mechanisms underlying the effects of AQPs on cold response in ticks. Results The amino acid sequence of AQPs shows high homology in Ixodida, with HlAQP2 and HlAQP5 proteins comprising two asparagine-proline-alanine (NPA) motifs, whereas HlAQP3 protein was featured by glycerol facilitator GlpF channel. The spatiotemporal expression of AQPs in H. longicornis varied significantly after low temperature treatment, and different expression patterns were observed over prolonged exposure periods. RNAi knockdown of AQPs significantly increased tick mortality after treatment at a sublethal temperature of − 14 °C for 2 h. Proteomic and transcriptomic analysis revealed that the differentially expressed genes and proteins caused by the knockdown of AQPs are mainly enriched in the fatty acid metabolism pathway. Conclusions The above results indicated that AQPs could regulate tick cold response by modulating water balance and fatty acid metabolism. Graphical Abstract